Agency Problem, Corporate Governance Mechanisms and Cost Stickiness in Firms Listed in Tehran Stock Exchange - saeid jabbarzadeh kangarluei; Morteza Motavassel; Amin Rahimzadeh Khazaei (راهبرد مدیریت مالی, 2015)
This research investigates the impact of the agency problem and the corporate governance mechanisms on cost stickiness in firms listed in Tehran Stock Exchange. To do so, 125 listed firms of Tehran Stock Exchange are selected as a sample to be studied during the period 2006-2014. Free Cash Flow (FCF), CEO Tenure, CEO Horizon and CEO Bonus are proxies for agency problem in this study. The results indicate that none of Free Cash Flow (FCF), CEO Tenure, CEO Horizon and CEO Bonus affects (administrative, general, sale) cost stickiness. The result also shows that corporate governance has no effect on the relationship between agency problem and (administrative, general, sale) cost stickiness.